Socio-Juridical Analysis of Advocates Obstructing The Investigation Process of Criminal Acts of Corruption - Abdul Wahid (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Advocates are one of the pillars of upholding the rule of law and human rights that provides legal services. They can act as a companion, give legal opinions or become a legal representative for and on behalf of his client. Advocates take refuge behind the right of immunity that they cannot be prosecuted civilly and criminally. They are guaranteed by law that there are advocates who obstruct or impede the investigation of criminal acts of corruption. Advocate immunity rights apply as long as carrying out their duties and profession in good faith but may not conflict with laws. Advocates who obstruct the investigation of criminal acts of corruption are contrary to ethics and contradict Article 21 and Article 22 of Law Number 20 of 2001 concerning the Eradication of Corruption Crimes.